Post-harvest disease management techniques in citrus fruits - Chávez Caicedo , Cristhian Jesús (2023)
Worldwide, citrus production has increased due to the growing demand from producing and exporting countries. However, postharvest losses are a challenge for citrus growers, especially those caused by the fungi Penicillium digittaum and P. italilicum; in addition to the microorganisms that cause pre-harvest diseases, which persist over time and occur during citrus storage. The objective of the research was to compile systemic, applicable and useful information on postharvest disease management techniques for citrus fruits (Citrus spp.) in Ecuador. One of the management techniques is the use of synthetic fungicides, especially Imidazole and Benzimidazole and salts such as sodium orthophenyl phenate. Among the biological options, fungi, bacteria and yeasts with antagonistic and antifungal capacity are used. Among the physical measures, storage under low temperature conditions is used, which varies according to citrus species and luminosity, and is suggested as an excellent management measure for the rot-causing fungi, P. digitatum and P. italicum. Postharvest disease management should have a plan that includes at least two control measures.